The emerging role of the HTRA1 protease in brain microvascular disease - Haffner, Christof (Frontiers in Dementia, 2023)
Pathologies of the brain microvasculature, often referred to as cerebral small-vessel disease (SVD), are important contributors to vascular dementia, the second most common form of dementia in aging societies. In addition to their role in acute ischemic and hemorrhagic stroke, they have emerged as major cause of age-related cognitive decline in asymptomatic individuals. A central histopathological finding in these pathologies is the disruption of the vessel architecture including thickening of the vessel wall, narrowing of the vessel lumen and massive expansion of the mural extracellular matrix. The underlying molecular mechanisms are largely unknown, but from the investigation of several disease forms with defined etiology, high temperature requirement protein A1 (HTRA1), a secreted serine protease degrading primarily matrisomal substrates, has emerged as critical factor and potential therapeutic target. A genetically induced loss of HTRA1 function in humans is associated with cerebral autosomal-recessive arteriopathy with subcortical infarcts and leukencephalopathy (CARASIL), a rare, hereditary form of brain microvascular disease. Recently, proteomic studies on cerebral amyloid angiopathy (CAA), a common cause of age-related dementia, and cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukencephalopathy (CADASIL), the most prevalent monogenic small-vessel disease, have provided evidence for an impairment of HTRA1 activity through sequestration into pathological protein deposits, suggesting an alternative mechanism of HTRA1 inactivation and expanding the range of diseases with HTRA1 involvement. Further investigations of the mechanisms of HTRA1 regulation in the brain microvasculature might spawn novel strategies for the treatment of small-vessel pathologies.